Worker Voice: Employee Representation in the Workplace in Australia, Canada, Germany, the UK and the US, 1914–1939 - Rees, Jonathan (Labour / Le Travail, 2017)
The article reviews the book, "Worker Voice: Employee Representation in the Workplace in Australia, Canada, Germany, the UK and the US, 1914–1939," by Greg Patmore.